Research trend on dyscalculia by bibliometric analysis during 2017-2022 - Deda, Yohanis Ndapa; Disnawati, Hermina; Ekawati, Rooselyna; Suprapto, Nadi (International Journal of Evaluation and Research in Education (IJERE), 2024)
Dyscalculia is the inability to perform simple numerical calculations in everyday life. However, no one has researched this topic worldwide in about two years. This study aimed to investigate the research trends on dyscalculia through bibliometric studies and research issues related to dyscalculia in the Scopus database starting 2017 to October 2022. The sample consisted of 536 total documents. The results showed that scientific publications on dyscalculia fluctuated. In the next five years, its movements cannot be predicted. The highest number of document types is articles, which is 369. The number of cross-border documents from 2017 to 2022 is in the United States, as many as 75 papers, and in Italy, 74 copies. These two countries are more dominant on the topic of dyscalculia. Furthermore, 536 documents comprising 94.4% of articles were used in English. In general, in research on dyscalculia, researchers produce four out of five significant clusters: patient, approach, task, and grade. However, topics related to dyscalculia and mathematics often studied are deficit students, deficit addition and subtraction, mathematics difficulty, instruction, and primary school. The results can be used to shed light on developing tendencies in dyscalculia investigations and suggest directions for future studies.